Logistics 4.0: Do we have professionals prepared from an Education 4.0? - Schettini Pinto, Carlos Alberto (International Journal of Scientific Research and Management (IJSRM), 2021)
With the advent of Industry 4.0, from 2011, it is clear that many areas had to adapt to the changes that came with the 4th Industrial Revolution. Having professionals prepared for the characteristics inherent to this new situation becomes a sine quae non for this highly connected and globalized environment. However, generations X, Y and Alpha are quite collimated with these new technologies since they are born in digital environments and have, from an early age, access to technologies. However, people from older generations, if they are not immersed and interested in the continuity of digital learning, end up becoming digitally illiterate and unable to act in technologically active environments. Thus, this article asks, do we have professionals prepared for education 4.0? In addition, it presents a flow to be adopted in any academic area aimed at applying the characteristics of education 4.0.